Las competencias genéricas en estudiantes de ingeniería: estudio del grado de adquisición y desarrollo de la capacidad de autorregulación del aprendizaje - Buffa, Fabián Alejandro (2021)
In the present work, the degree of acquisition of self-regulated learning (SRL) in students from the first and the fifth year of different Engineering careers at the National University of Mar del Plata (UNMDP) is described. The studies were exploratory and descriptive in nature, with an ex post facto design. The instrument used was the Motivation and Learning Strategies Questionnaire (MSLQ) (Pintrich, 1991). The results from the dimension "Cognitive and Metacognitive Strategies" are presented, in their corresponding subdimensions: Essay; Elaboration; Organization; Critical thinking; Metacognitive selfregulation. The participants were approximately 300 first-year students and 100 fifth-year students from the Faculty of Engineering. The answers of the questionnaire were analyzed, carrying out univariate descriptive statistics through graphs and descriptive statistics of each of the ordinal categorical variables involved. Although 5th year students show some development in some SRL-related competencies, they are still far from desirable. Given that these skills are not innate or intuitive, but rather need to be taught and learned, it will be necessary to incorporate them into the programs of the different subjects of the Engineering careers at the UNMDP and to design different strategies able to make explicit self-regulated learning.